2006
DOI: 10.1021/jp0551059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures and Electronic Transitions of 3,6-Diphenyl-1,2-dithiin and Its Radical Cation:  A Spectroelectrochemical and DFT Study

Abstract: One-electron oxidation of 3,6-diphenyl-1,2-dithiin yields the corresponding radical cation. The product is stable at low temperatures and can be distinguished by a triplet EPR signal. Cyclic voltammetric, UV-vis spectroelectrochemical, and DFT studies were performed to elucidate its molecular structure and electronic properties. Time-dependent DFT calculations reproduce appreciably well the UV-vis spectral changes observed during the oxidation. The results reveal a moderately twisted structure of the 1,2-dithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Hence, it has been used to study the electron spectra of numerous systems including closed-shell and open-shell systems. The accuracy and reliability of spin-unrestricted time-dependent density functional theory for open-shell systems have been tested by studying both the organic and transition mental compounds [39][40][41][42][43][44][45][46][47][48]. The ground states of these systems studied here have only one unpaired electron and thus doublet states.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it has been used to study the electron spectra of numerous systems including closed-shell and open-shell systems. The accuracy and reliability of spin-unrestricted time-dependent density functional theory for open-shell systems have been tested by studying both the organic and transition mental compounds [39][40][41][42][43][44][45][46][47][48]. The ground states of these systems studied here have only one unpaired electron and thus doublet states.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 1 and 2 2+ are 1,2-dithiins. The electrochemistry of a number of other 1,2-dithiins has been investigated, but those studies have emphasized oxidations, while the current study will focus on the reduction of these compounds and cleavage of the S–S bond. The reductions of 1 and 2 2+ are of particular interest because they can be viewed as having two sites for reduction: the bipyridine/bipyridinium and disulfide moieties which may interact with each other.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that various types of six membered 1,4-dihydroheterocycles posses a high conformational flexibility using ab initio calculation [6]. Among cyclohexadiene, the dithiine and its derivatives have extensively been studied [7][8][9][10]. In follow up on our works [11][12][13], we are especially interested to study of optimized conformations of 1,4-dithiine and S-oxygenated derivatives.…”
Section: Introductionmentioning
confidence: 99%